The Health Education Regarding Basic Life Support (BLS) According To AHA 2020 On The Level Of Knowledge And Skills Of Health Personnel - Kamesyworo, Kamesyworo; Haryanti, Eka (Chakra Brahmanda Lentera Institute, 2023)
Background: An emergency is a condition or situation in which there is a threat of danger or where the negative impact of that danger has occurred, which results in further damage. These emergencies and emergencies require quick action outside of daily activities using different special methods and procedures. This research aims to determine the influence of health education regarding basic life support according to the AHA 2020 on the level of knowledge and skills of health workers at the Pagar Agung Lahat Community Health Center in 2023. Methods: The research method used was quasi-experimental with a one-group pretest-posttest design. The total sample was 25 health workers. Based on statistical output results paired with Sample Delivery of results from the pretest and posttest, this shows an increase in the knowledge of Health Officers at the Pagar Agung Lahat Community Health Center. Results: The T-test results are valuable p=,000 (<.0.5), so it can also be concluded that health education influences basic life support, according to AHA 2020. Meanwhile, for skills before the intervention, data on skilled Health employees was 8%, whereas after the intervention was given, there was an increase, which is quite significant at 80% for the skilled. Based on test Paired Sample T-test From the p-value = 0.000 (<0.5), it can also be concluded that there is an influence of health education regarding basic life support, according to AHA 2020 on the skills of Health Workers at the Pagar Agung Lahat Community Health Center in 2023. Conclusion: there is an influence health education to level knowledge and skills on health workers at the Pagar Community Health Center Great Everything